OPTIMIZING THE TREATMENT OF RICKETS IN INFANTS (Academia Science Repository, 2023)
Rickets is not only a pediatric, but also a medical and social problem, as it has serious consequences that cause a high incidence of children. Vitamin D - deficiency rickets is a disease of children caused by vitamin D deficiency in the body, occurring with metabolic disorders, both phosphorus-calcium and lipid, affecting primarily the bone and nervous systems. Improper treatment and prevention of rickets contribute to the disruption of the formation of the skeletal system, a decrease in motor activity, immune defense, a delay in neuropsychic and physical development, and the development of frequent acute respiratory diseases. The examined patients revealed significant changes in the composition of higher fatty acids and the depth of changes in the composition of higher fatty acids depended on the severity of rickets. The revealed violations of the composition of higher fatty acids were corrected with the help of vegetable (apricot) oil and aevit. The results of the use of corrective therapy with apricot oil and aevit for the treatment of children with rickets are presented. The effectiveness of this method of treatment of children with rickets is shown.